Public expenditure, policy coordination, and regional inequality - Susanne Soretz; Ingrid Ott (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We analyze within a spatial endogenous growth setting the impact of public policy coordination on regional inequality. Governments in each of the two symmetric regions provide a local public input that becomes globally effective due to integration. Micro-foundation of governmental behavior is based on three different coordination schemes: autarky, full or partial coordination. The "optimal" size of the local public inputs - as measured by the expenditure share ratios - differs depending upon the extent to which the governments take interregional interdependencies and feedback effects into account. The resulting spatial distribution of economic activity is driven by integration, which acts as dispersion force, and scale effects, which act as concentration force. The latter are drivers of regional inequality. Given full symmetry, local externalities cancel w.r.t to their impact on spatial concentration. We show that coordination of public decisions that base on productivity considerations unequivocally foster concentration and destabilize the spreading equilibrium. Regional inequality is thus an optimal result or put differently, the convergence goal can only be met by applying additional arguments.
Keywords: H10; E60; O40; R50; 330; policy coordination; income convergence; bifurcation